Macrophages as a Cell-Based Therapy for Liver Disease - Starkey Lewis, Philip J.; Moroni, Francesca; Forbes, Stuart J. (Seminars in Liver Disease, 2019)
Liver failure arising from acute and chronic liver disease is an unmet clinical need that urgently requires novel therapeutic options in addition to orthotopic liver transplantation. Cell therapies offer new strategies to recover liver function through the reconstitution of healthy parenchyma and resolution of tissue pathology. Macrophages are professional phagocytes that comprise a key part of the innate immune system providing an important defense mechanism against invading pathogens. Macrophages are an inherently diverse cell type with respect to ontogeny, tissue distribution, phenotype, and function. The ability of macrophages to afford innate immunity, efficiently scavenge apoptotic/necrotic cells, and modulate local tissue microenvironment makes them an attractive cell therapy candidate for various diseases. This review aims to outline the rationale and utility of macrophages to serve as a potential cell therapy for liver disease.
Keywords: macrophages; cirrhosis; acetaminophen; liver immunology; cell therapy